Agreement with Ritsumeikan University (Institutional Knowledge at Singapore Management University, 2000)
On the first day of classes, Singapore Management University launched its international exchange programme for students by signing a memorandum of understanding with Ritsumeikan Asia Pacific University from Oita Prefecture, Japan. This is the first of many agreements with overseas institutions to increase the global perspective and cultural experiences of SMU undergraduates. Photo taken on 1 August 2000.